Catholics across borders: Canadian immigrants in the North Country, Plattsburgh, New York, 1850-1950 - Richard, Mark Paul (SUNY Press, 2024)
"Illuminates the crossborder migration and settlement of Catholics from Canada to northern New York in the period from 1850 to 1950"--